Pengaruh Media Kata Bergambar dalam Mengupayakan Kemampuan Pra-Membaca Permulaan pada Anak Kelompok B di TK Insan Cemerlang Kota Makassar - Wahyuna Wahyuna; Sri Sufliati Romba; Musfira Musfira (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The core issue of this study focuses on the impact of media featuring illustrated words on the pre-reading skills of children in group B at TK Insan Cemerlang in Makassar City. The aim of this research is to determine the extent to which illustrated word media affects the pre-reading abilities of children in group B at the preschool. The methodology employed in this study involves conducting an experiment with a single group design, which includes both pre-tests and post-tests. he research sample is made up of 14 children from the B2 class at TK Insan Cemerlan To gather data, the researcher implemented a checklist technique to assess pre-reading development. Data collection methods included observation, interviews, and documentation. Data analysis was conducted utilizing the Wilcoxon Signed Rank Test, assisted by IBM SPSS 25 software. The findings of the study indicate a significant effect on children's pre-reading skills after they were exposed to the illustrated word media. The average score for the pre-test was 5. 5, while the average score for the post-test rose to 13. Analysis of the data using the Wilcoxon Signed Rank Test yielded an Asymp. sig (2-tailed) value of 0. 01, indicating a probability below 0. 05.